Results of a Pilot Study to Ameliorate Psychological and Behavioral Outcomes of Minority Stress Among Young Gay and Bisexual Men. Issue 5 (September 2017) - Smith, Nathan Grant; Hart, Trevor A.; Kidwai, Ammaar; Vernon, Julia R.G.; Blais, Martin; Adam, Barry
Abstract: Project PRIDE (Promoting Resilience In Discriminatory Environments) is an 8-session small group intervention aimed at reducing negative mental and behavioral health outcomes resulting from minority stress. This study reports the results of a one-armed pilot test of Project PRIDE, which aimed to examine the feasibility and potential for efficacy of the intervention in a sample of 33 gay and bisexual men aged 18 to 25. The intervention appeared feasible to administer in two different sites and all participants who completed posttreatment ( n = 22) or follow-up ( n = 19) assessments reported high satisfaction with the intervention. Small to large effect sizes were observed for increases in self-esteem; small effect sizes were found for decreases in loneliness and decreases in minority stress variables; and small and medium effect sizes were found for reductions in alcohol use and number of sex partners, respectively. Overall, Project PRIDE appears to be a feasible intervention with promise of efficacy. Highlights: An 8-session group intervention was developed for young gay and bisexual men to reduce negative outcomes of minority stress A 1-armed pilot of the intervention enrolled 33 gay and bisexual men, aged 18-25, of which 22 completed the intervention The intervention appeared feasible to administer and participants reported high satisfaction Posttest and follow-up assessments revealed effects in the expected direction for most outcomes